Numerical Solutions for Convective Boundary Layer Flow of Micropolar Jeffrey Fluid with Prescribe Wall Temperature - Noraihan Afiqah Rawi; Nor Athirah Mohd Zin; Asma Khalid; Abdul Rahman Mohd Kasim; Zaiton Mat Isa; Sharidan Shafie (IndoMS, 2020)
The steady two dimensional convective boundary layer flow of micropolar Jeffrey fluid past a permeable stretching sheet is studied in this paper. The governing boundary layer equation in the form of partial differential equations are transformed into nonlinear coupled ordinary differential equations and solved numerically using an implicit finite-difference scheme known as Keller-box method. The effects of Prandtl number, Deborah number, and material parameter with the boundary condition for microrotation, n = 0 (strong concentration of microelements) on the velocity, microrotation, temperature profiles as well as the skin friction and heat transfer coefficients are presented and discussed. An excellent agreement is observed between the present and earlier published results for some special cases. The results revealed that, the effect of Deborah number and stretching parameter are increased the heat transfer coefficient while the opposite trend is observed for the effects of material and velocity slip parameters. It was also observed that, the values of skin friction increased with the increment on the values of all studied parameters.